1985
DOI: 10.3758/bf03197685
|View full text |Cite
|
Sign up to set email alerts
|

Automatic and strategic effects in semantic priming: An examination of Becker’s verification model

Abstract: Becker's (1980) verification model, in conjunction with a two-strategy hypothesis, is cited as an alternative to a dual-process model (e.g., Posner & Snyder, 1975) of word recognition and semantic priming. Becker's approach suggests that individuals can use either an "expectancy" or a "prediction" strategy in word recognition, and maintains that the verification model successfully predicts certain patterns of facilitation and inhibition in a semantic priming task that a dual-process model cannot. The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
29
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 31 publications
(44 reference statements)
7
29
0
Order By: Relevance
“…In this regard, it is interesting that with the samematerials usedhere, Neelyet al (1989) obtained a 16-msec inhibition effectfor high-dorninance exemplars (p < .05, one-tailed) and a 2I-msec inhibition effectfor low-dominance exemplars (p < .05, two-tailed) in the unrelated priming condition in their RP(.88)/NR(.89) group, in which expectancy should have been operating due to the high relatedness proportion. Although substantial inhibition typically occurs in unrelatedpriming conditions in the LDT when category names are used as primes and both high-and low-dominance exemplars are used as related targets, inhibition does not occur in lists in which related primes and targets are always strongly associatively related (e.g., see Becker, 1980, den Heyer, Briand, & Smith, 1985, Smith, Briand, Klein, & den Heyer, 1987). Becker's (1980) expectancy theory explains inhibition as being due to subjects' wasting their time unsuccessfully searching the expectancy set following unrelated primes, relative to the neutral priming condition in which there is no expectancy set to waste time searching through.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is interesting that with the samematerials usedhere, Neelyet al (1989) obtained a 16-msec inhibition effectfor high-dorninance exemplars (p < .05, one-tailed) and a 2I-msec inhibition effectfor low-dominance exemplars (p < .05, two-tailed) in the unrelated priming condition in their RP(.88)/NR(.89) group, in which expectancy should have been operating due to the high relatedness proportion. Although substantial inhibition typically occurs in unrelatedpriming conditions in the LDT when category names are used as primes and both high-and low-dominance exemplars are used as related targets, inhibition does not occur in lists in which related primes and targets are always strongly associatively related (e.g., see Becker, 1980, den Heyer, Briand, & Smith, 1985, Smith, Briand, Klein, & den Heyer, 1987). Becker's (1980) expectancy theory explains inhibition as being due to subjects' wasting their time unsuccessfully searching the expectancy set following unrelated primes, relative to the neutral priming condition in which there is no expectancy set to waste time searching through.…”
Section: Discussionmentioning
confidence: 99%
“…Passerieux et al (1995) employed an LDT with SOAs of 64 or 240 ms, and a 33% relatedness proportion, in a study of 17 schizophrenia participants (which were also grouped by clinical subtype) and 11 normal controls. While the 240-ms SOA is identified as a "controlled" condition by the authors, it should be noted that this SOA is generally considered too short to permit the emergence of true controlled information processing (e.g., deGroot, 1984; den Heyer et al, 1985;Neely, 1977Neely, , 1991. Nonsignificant semantic priming was observed for both schizophrenia and control groups at an SOA of 64 ms. At the 240 ms SOA, the control group showed the expected inhibition for unrelated Manschreck et al, 1988 TD: 250 ms SOA 561 6 178 478 6 176 91 6 n.a.…”
Section: Evidence For Normal Automatic Information Processing In the mentioning
confidence: 99%
“…What work has been done has involved slow decision processes, likely to involve conscious processing, Neely's (1977) original investigation of relations in semantic memory found that subjects required considerable time to switch to the relation defined by instructions as correct. Other experimenters have found significant effects of the proportions of different kinds of pairs of words in a list, but only when the stimulus onset asynchrony (SOA) between the first and the second word of a pair was quite long (e.g., I,000 msec; Becker, 1980;den Heyer, Briand, & Smith, 1985;Neely, Keefe, & Ross, 1989;see Neely, 1991, for a review).…”
Section: Lexical Decisionmentioning
confidence: 99%